INVESTMENT SELECTION AND EVALUATION FOR CHINA EXPRESS DELIVERY MARKET - Wang, Xiaojia; Chen, Wei; Lekse, William John (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
China’s express industry has experienced phenomenal growth in recent years. More investors are considering entering the express delivery industry in China. Investors are particularly interested in understanding the following questions: 1) How do existing express delivery companies in China manage their businesses? 2) What are the strengths and weaknesses of these companies if there is potential collaboration? This study investigates the top 12 express delivery companies in China and independently evaluates their business performance. To this end, we first employ the uncertain linguistic variables (ULV) to simulate the uncertainties of a decision-making process. Then, we propose a novel weighted method integrating subjective and objective evaluations into a unique value and rank the 12 express delivery companies. Compared with conventional methods, the proposed model mitigates the adverse effects of uncertainty while providing a practicable approach to incorporate the sentiments of area experts. This model can be easily applied to other industries and markets.